Concomitant Use of Single Suture Anchor and Transosseus Repair Provide Optimal Results in Simultaneous Bilateral Quadriceps Tendon Rupture: A Case Report - Albar, Husnul Fuad; Yudhadibrata, Permana; Widjaja, Arya Cipta (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction Bilateral quadriceps tendon rupture is a rare condition and often associated with underlying medical comorbidities such as chronic renal insufficiency. This case report is aimed to evaluate the surgical outcome using the combination of suture anchor and transosseus repair technique. Presentation of Case Presenting a 54-year-old male who sustained simultaneous bilateral quadriceps tendon rupture with history of right nephrectomy and chronic kidney disease requiring intermittent hemodialysis. He came with sudden bilateral knee pain, history of falling, and inability to walk since three weeks before admission to the hospital. Tenderness above the superior pole on both patella, accompanied with slight swelling and no active range of motion (ROM) of either knee joint was found on physical examination. Complete rupture of the quadriceps tendon of both knees at their osseus-tendon junction were revealed on magnetic resonance imaging (MRI). Discussion Recent literatures suggested that transosseus technique offers the safest and more stable tendon reattachment, while suture anchor provides biomechanical superiority. We tried to combine these advantages by incorporating both methods. Progressive active knee motion exercise was performed shortly after using the Kocher slab for 2 weeks.Subsequently, the patient can achieve painless, active extension and active 90°-120° knee flexion 1 month post-operatively. Conclusion The application of a single suture anchor with transosseus repair in quadriceps tendon rupture led to an optimal outcome, improved stability, and earlier rehabilitation.